Historical literacy competence as a type of media literacy among German language undergraduate students - Chang, Shi Wen (2019)
A current development in Malaysia: the young generation is exposed to an overwhelming number of media (e.g. social media, printed media, broad-cast, film) on daily basis. The convenience of internet access has resulted in the dependency of people towards online information without critically judging its reliability. The study of this development indicates that the young generation lacks media literacy competencies. As part of media literacy (ML), historical literacy (HL) plays an important role in strengthening the development of media literacy among people. When it comes to foreign language learning, historical literacy competencies are particularly important, because one of the best ways to learn a foreign language comprehensively is to understand the culture including the history of that particular target language. Leveraging on historical feature film to learn history has become a common approach in the education field, the development of historical literacy competencies becomes essential in helping learners to critically understand and regard historical feature film as learning material. The purpose of this study is to describe the current state of the historical literacy competencies (HLC) among students. This study focuses on evaluating the dimension of HLC, which includes content knowledge (CK), narrative analysis (NA) and historical empathy (HE) among the participants. There are two research questions for this study, which are: (1) what is the current state of the participant’s historical literacy competencies (HLC) by evaluating its dimensions (CK, NA and HE) among them?; and (2) how have content knowledge (CK), narrative analysis (NA) and historical empathy (HE) contributed to historical literacy competencies (HLC)? This study applied a descriptive case study method, with a group of 21 students as participants. A class project called “Exploring World War II – A Historical Feature Film Project” with 7 historical feature films and face-to-face interviews was applied as the instrument in this study. The data collected were analysed using inductive approach. The findings from this study indicated that content knowledge, narrative analysis, and historical empathy have fairly displayed among the students. Additionally, the findings also signified that content knowledge, narrative analysis, and historical empathy contributed to the historical literacy competencies via critical thinking. Results from this study will provide an insight for the researcher that interested in explore historical literacy as part of media literacy.